(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
the article considers innovations introduced in the system of ensuring public order and safety, prevention of offenses, broad public participation in reducing accidents and fatalities on the roads in accordance with the Concept of Public Safety of the Republic of Uzbekistan and the practice of its implementation